Perceptions in Trimester III About Covid-19 Scrining Using Rapid Test Antibody: Persepsi Ibu Hamil Trimester III Mengenai Skrining Covid-19 Menggunakan Rapid Test Antibody - Ertiana, Dwi; Anggraini, Wulan (Jurnal Kebidanan Midwiferia, 2023)
Rapid antibody test is one method of screening for Covid-19 in third trimester pregnant women during the pandemic. The low participation of pregnant women in the third trimester in the implementation of Covid-19 screening can be seen from the delay in pregnant women carrying out rapid antibody tests. The purpose of the study was to find out the Perception of Pregnant Women in the Third Trimester Regarding Screening for Covid-19 Using Antibody Rapid Tests. The research design used a descriptive method. The variable is the perception of pregnant women in the third trimester regarding Covid-19 screening using a rapid antibody test. The population is 40 people and the number of samples is 29 respondents who are taken by purposive sampling. The research was carried out on April 20 - May 22, 2021 at the Kusuma Pertiwi Clinic, Kepung Village, Kepung District, Kediri Regency. The results showed that the perception of pregnant women in the third trimester about screening for Covid-19 using a rapid antibody test was mostly negative. 17 pregnant women in the third trimester (52%), the negative perception was almost entirely influenced by the education of 18 respondents (62%). The negative perception of pregnant women in the third trimester about screening for Covid-19 using rapid antibody tests is influenced by negative information for pregnant women about rapid antibody tests, causing negative perceptions about the process of implementing the Covid-19 screening, pregnant women's trust in hoax news caused by the information provided to them. less than optimal pregnant women.